Shift of keratin expression profile in end-stage kidney increases the risk of tumor development - Sarlós, Donát Péter; Kovacs, Gyula (Anticancer research, 2018)
Background/Aim: Pre-neoplastic lesions and renal cell tumors of distinct pheno- and genotypes occur frequently in end-stage kidneys. The aim of this study was to investigate the role of KRT7 and KRT19 in this process, the expression of which was previously detected by Affymetrix GeneChip analysis. Patients and Methods: Twelve end-stage kidneys were analyzed to find pre-neoplastic lesions and tumors and expression of KRT7 and KRT19 was examined by immunohistochemistry. Results: A total of 17 tumors, 149 pre-neoplastic lesions, 179 simple or proliferative cysts >2 mm were identified. Diffuse expression of KRT7 and KRT19 was seen in all end-stage kidneys as well as in the vast majority of cysts, pre-neoplastic lesions and tumors. Conclusion: Our data indicates that de novo expression of KRT7 and KRT19 resulting in altered plasticity and stem cell characteristics of epithelial cells might be a crucial factor in increasing the risk of tumor development in end-stage kidneys.
Gesehen am 21.05.2019